PIMIKIRAN ABRAHAM MASLOW TENTANG MOTIVASI DALAM BELAJAR - Dedi Dwi Cahyono; Muhammad Khusnul Hamda; Eka Danik Prahastiwi (TAJDID: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2022)
Motivation is needed every day by students, especially from outside themselves to have a passion for learning. The feeling of laziness felt by students makes them not enthusiastic in participating in learning in class. Absorbing so many materials and lessons requires the intention and seriousness of a student. Various features that interfere with the arrival of smartphone technology that has a big impact on students. Teachers and parents have an important role to have a positive influence in following each lesson. There are several ways that can motivate students by giving awards, prizes, or praise for those who have tried to learn. This method provides a stimulus to be more enthusiastic in achieving goals with several rewards. Abraham Maslow's theory explains that a person has needs such as eating, drinking and so on. Needs must be met as well as student learning must have a sense of need to do so.